O możliwościach i znaczeniu kształcenia przyszłego personelu szkół w duchu kazien na przykładzie Pracowni Dydaktyki Fizyki - Sujak-Cyrul, Barbara; Dudziak-Kamieniarz, Sylwia (On Possibilities and Importance of Education for School Future Personnel in the Spirit of Kaizen - a Case Study of Physics Didactic Laboratory, 2008)
The paper, referring to Japanese experiences of effective managers' and workers' education in the spirit of kaizen and the need for implementation of training of such attitudes in Polish schools, presents it practice - on the example of future physics teachers' education in Physics Didactic Laboratory - possibilities and importance of parallel shaping of such way of thinking as well as attitudes of active search for improvement "by small steps" within the framework of an existing unitary educational process in high school. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 88-117